Boosting catalytic efficiency of nanostructured CuO-supported doped-CeO2 in oxidative coupling of benzyl amines to N-benzylidenebenzyl amines and benzimidazoles: impact of acidic and defect sites - Sakinala, Sailatha; Kothoori, Naga Pranava Sree; Jeedi, Suman; Varkolu, Mohan; Baithy, Mallesham (Frontiers in Nanotechnology, 2025)
This study presents the rational synthesis of Cu-supported doped-CeO2 catalysts designed for the oxidation of benzylamine, both in the absence and presence of 1,2-diaminobenzene. The catalysts were prepared using a two-step method and characterized by various techniques, including XRD, Raman spectroscopy, BET surface area analysis, NH3-TPD, pyridine-FTIR, H2-TPR, XPS, SEM, and TEM. Raman and XPS analyses confirmed the presence of oxygen vacancy sites, with CuO/CeO2-ZrO2 displaying the highest concentration of these sites. H2-TPR revealed strong metal-support interactions, while NH3-TPD indicated that CuO/CeO2-ZrO2 possessed the greatest number of acidic sites. The pyridine-FTIR results indicates both the acidic sites present on the catalyst surface. The Cu/CeZr sample exhibits the lowest Iu////ITotal ratio (0.0567) compared to the Cu/Ce (0.0843) and Cu/CeSi (0.0672) samples, indicating a higher number of Ce3+ species or a greater number of oxygen defect sites in the sample. The catalyst demonstrated excellent performance in converting benzylamine to imines and was also highly effective in the synthesis of benzimidazole from benzylamine and 1,2-diaminobenzene, broadening its application potential. The superior catalytic activity is attributed to the abundant oxygen vacancies, redox properties, strong metal-support interactions, and acidic sites. Furthermore, the CuO/CeO2-ZrO2 catalyst maintained its efficiency over five consecutive cycles, exhibiting robustness, high functional group tolerance, and reduced reaction times, making it a promising system for diverse catalytic applications.